Ag2S / Mn0. 5Cd0. 5S composite catalyst as well as preparation method and application thereof

By recombining Ag2S with Mn0.5Cd0.5S, an Ag2S/Mn0.5Cd0.5S composite catalyst was formed, and the problem of rapid recombination of photogenerated holes and electrons by CdS photocatalysts was solved, achieving more efficient photocatalytic hydrogen production and CO2 reduction and CO production.

CN119549165AActive Publication Date: 2025-03-04CHANGZHOU UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411733839.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-03-04
Estimated Expiration
2044-11-29

AI Technical Summary

Technical Problem

In practical applications, CdS photocatalysts face the problem of rapid recombination of photogenerated holes and photogenerated electrons, resulting in low photocatalytic hydrogen production efficiency.

Method used

By recombining Ag2S with Mn0.5Cd0.5S, an Ag2S/Mn0.5Cd0.5S composite catalyst is formed, and its heterojunction structure and wide spectrum absorption capacity are used to improve the photocatalytic performance.

Benefits of technology

The catalytic performance and light absorption capacity are improved, the separation efficiency of photogenerated carriers and holes is enhanced, and the efficiency of photocatalytic hydrogen production and CO2 reduction is significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005160984950000051
    Figure BDA0005160984950000051
  • Figure HDA0005160984960000011
    Figure HDA0005160984960000011
  • Figure HDA0005160984960000012
    Figure HDA0005160984960000012
Patent Text Reader

Abstract

The invention belongs to the field of piezoelectric electro-catalysis, and particularly relates to an Ag2S / Mn0. 5Cd0. 5S composite catalyst as well as a preparation method and application thereof. Mn0. 5Cd0. 5S nanoparticles and Ag2S are prepared by a hydrothermal synthesis method, and finally, the Mn0. 5Cd0. 5S nanoparticles and Ag2S are compounded by an impregnation method to form a heterojunction, so that the Ag2S / Mn0. 5Cd0. 5S composite catalyst is prepared. The catalyst is used for reducing H2 and CO2 produced by piezoelectric electro-catalysis under the synergistic effect of sunlight irradiation and ultrasonic vibration. The synthesis method of the catalyst is simple, green, pollution-free and high in operability. The prepared catalyst has abundant active sites and an excellent catalytic effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of piezoelectric photocatalysis, and specifically relates to an Ag2S / Mn 0.5 Cd 0.5 S composite catalyst and its preparation method and application. Background Art

[0002] In recent years, with the booming economy and the continuous expansion of population, energy shortage and environmental protection issues have become increasingly prominent and have become the focus of global attention. In this context, it is particularly urgent and important to promote the development of sustainable and clean energy. Among many candidate energy sources, hydrogen energy stands out with its high energy density and environmental friendliness, becoming a hot topic of research. In particular, CdS, as a metal sulfide photocatalyst, has received extensive attention and research in the past few decades due to its suitable band gap characteristics. However, despite its great potential, CdS faces the challenge of rapid recombination of photogenerated holes and photogenerated electrons in practical applications, which greatly limits its efficiency in photocatalytic hydrogen production. In order to overcome this problem, scientists have turned their attention to Mn x Cd 1-x S solid solution. This material achieves flexible control of the band gap by adjusting the ratio of Mn to Cd, which not only retains the excellent properties of CdS, but also significantly improves the photocatalytic activity and corrosion resistance. x Cd 1-x S solid solution is regarded as a highly potential substitute, which is expected to play an important role in future energy conversion and environmental protection and show broad application prospects.

[0003] Ag2S has high chemical stability and can maintain the stability of its structure and performance under various environments. At the same time, Ag2S also has the characteristics of low toxicity or non-toxicity, which makes its application safer and more environmentally friendly. Ag2S can absorb light in a wide range of spectra, including visible light and near-infrared light. x Cd 1-x S composite, aiming to provide a catalyst with better photocatalytic performance. Summary of the invention

[0004] The object of the present invention is to provide a Ag2S / Mn 0.5 Cd 0.5 S composite catalyst, and applied it to piezoelectric photocatalytic hydrogen production or CO2 reduction to produce CO. The prepared catalyst has higher catalytic performance and stronger light absorption ability.

[0005] The Ag2S / Mn 0.5 Cd 0.5 S composite catalyst is composed of Mn 0.5 Cd0.5 The heterojunction structure formed by the composite of S and Ag2S, Ag2S is Mn 0.5 Cd 0.5 The preparation method comprises the following steps:

[0006] (1) Mn 0.5 Cd 0.5 Preparation of S:

[0007] Mn(CH3COO)2·4H2O and Cd(CH3COO)2·2H2O were dissolved in deionized water and stirred until completely dissolved. Then C2H5NS(TAA) was added and stirred to mix evenly. The mixture was transferred to a reactor lined with polytetrafluoroethylene and placed in an oven at 160°C for 24 hours. After the reaction was completed, it was cooled to room temperature and filtered. The solid in the reactor was washed with deionized water and anhydrous ethanol for 3 times and dried at 60°C to obtain orange Mn 0.5 Cd 0.5 S powder. (Abbreviation: MCS).

[0008] Further, the molar ratio of Mn(CH3COO)2·4H2O and Cd(CH3COO)2·2H2O is 1:1;

[0009] Furthermore, the molar ratio of Mn(CH3COO)2·4H2O and C2H5NS is 1:2.

[0010] (2) Preparation of Ag2S

[0011] AgNO3 and TAA were dispersed in H2O and stirred for 20 min to mix them evenly. The mixture was then transferred to a reactor lined with polytetrafluoroethylene and placed in an oven at 150°C for 2 h. After the reaction was completed, it was cooled to room temperature. The solid in the reactor was washed and dried to obtain Ag2S.

[0012] Furthermore, the molar ratio of AgNO3 and TAA is 1:1.

[0013] (3) Ag2S / Mn 0.5 Cd 0.5 Preparation of S composite catalyst:

[0014] Mn 0.5 Cd 0.5 The S catalyst and Ag2S catalyst were dissolved in a solvent, ultrasonicated and stirred. Filtered, washed and dried at room temperature to obtain an orange powder, which is Ag2S / Mn 0.5 Cd 0.5 S composite catalyst.

[0015] Furthermore, the solvent is: deionized water, anhydrous ethanol, or a mixed solvent of anhydrous ethanol and water; the amount of Ag2S added is 0.5 Cd 0.5 S is 1 to 7% by mass (preferably 5%).

[0016] Furthermore, the ultrasonic power is 240 W, the ultrasonic time is 1 h, the stirring speed is 400 r / min, and the stirring is 4 h.

[0017] The composite catalyst prepared above is used for piezoelectric photocatalytic hydrogen production, and its specific application method is: weigh Ag2S / Mn 0.5 Cd 0.5 The S composite catalyst is added into water and evenly dispersed by ultrasound. Then, Na2S and Na2SO3 aqueous solutions are added as sacrificial agents. N2 is passed through and sealed to produce H2 under the common conditions of ultrasound and light.

[0018] The composite catalyst prepared above is used for CO2 reduction to produce CO. The specific application method is as follows: weigh Ag2S / Mn 0.5 Cd 0.5 The S composite catalyst is added into water and evenly dispersed by ultrasound. Then, Na2S and Na2SO3 aqueous solutions are added as sacrificial agents, CO2 is passed through, and CO is produced in a sealed manner under the common conditions of ultrasound and light.

[0019] The ultrasonic power is 240 W, and the light power is 55 W. The concentrations of Na2S and Na2SO3 in the sacrificial agent solution are 0.35 M and 0.25 M, respectively. The amount of the composite catalyst in water is 2 mg / 18 mL.

[0020] The present invention has the advantages that:

[0021] (1) Ag2S / Mn synthesized by the present invention 0.5 Cd 0.5 The S composite catalyst has simple synthesis conditions, is easy to operate, and has the characteristics of rapidity, high efficiency, energy saving and environmental protection.

[0022] (2) Ag2S has high chemical stability and can maintain the stability of its structure and performance under various environments. At the same time, Ag2S is also low in toxicity or non-toxic, which makes its application safer and more environmentally friendly. Ag2S can absorb light in a wide range of spectra, including visible light and near-infrared light. This shows that the composite catalyst has good crystallinity and purity.

[0023] (3) Ag2S and Mn of the present invention x Cd 1-x S has a different energy band structure and a wider light absorption range, which improves the utilization rate of light energy. The separation of photogenerated electrons and holes at the interface is also due to the interaction between Ag2S and Mnx Cd 1-x S tightly binds, thereby improving the photocatalytic efficiency.

[0024] (4) Ag2S / Mn synthesized by the present invention 0.5 Cd 0.5 S has a lower overpotential, smaller impedance and smaller Tafel slope, indicating that Ag2S / Mn 0.5 Cd 0.5 The separation efficiency of photogenerated carriers and holes in S is higher. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 It is hydrothermally synthesized Mn 0.5 Cd 0.5 S, Ag2S and X% Ag2S / Mn synthesized by impregnation method 0.5 Cd 0.5 S (where X is the ratio of Ag2S) XRD pattern of the composite catalyst;

[0026] Figure 2 It is Mn 0.5 Cd 0.5 S(MCS), Ag2S and 3%Ag2S / Mn 0.5 Cd 0.5 SEM image of S composite catalyst;

[0027] Figure 3 It is pure MCS and 3% Ag2S / Mn 0.5 Cd 0.5 LSV curve of S;

[0028] Figure 4 Pure MCS and 3% Ag2S / Mn 0.5 Cd 0.5 EIS curve of S;

[0029] Figure 5 It is pure MCS and 3% Ag2S / Mn 0.5 Cd 0.5 Tafel slope plot of S;

[0030] Figure 6 Pure MCS, Ag2S and 3% Ag2S / Mn 0.5 Cd 0.5 UV-vis spectrum of S;

[0031] Figure 7 Pure MCS and different ratios of Ag2S / Mn under piezoelectric-optical action 0.5 Cd 0.5 H2 production performance diagram of S composite catalyst;

[0032] Figure 8 Pure MCS and different ratios of Ag2S / Mn under piezoelectric action only 0.5 Cd 0.5 H2 production performance diagram of S composite catalyst;

[0033] Fig. 9 Pure MCS and different ratios of Ag2S / Mn under light only 0.5 Cd 0.5 H2 production performance diagram of S composite catalyst;

[0034] Fig.10 3% Ag2S / Mn with different Mn / Cd ratios under piezoelectric light x Cd 1-x H2 production performance diagram of S;

[0035] Fig.11 Pure MCS and different ratios of Ag2S / Mn 0.5 Cd 0.5 Performance diagram of CO2 reduction to CO production over S composite catalyst. DETAILED DESCRIPTION

[0036] The present invention is not limited to the following specific implementations. A person skilled in the art can implement the present invention in a variety of other specific implementations based on the content disclosed in the present invention, or any simple changes or modifications made to the design structure and ideas of the present invention fall within the protection scope of the present invention. It should be noted that the embodiments and features in the embodiments of the present invention can be combined with each other without conflict. The H2 and CO production efficiency is calculated according to the following formula:

[0037]

[0038] R: H2 / CO production rate, unit: μmol / (g·h), V: hydrogen / carbon monoxide volume, unit: μL, m: catalyst mass, unit: g, t: reaction time, unit: h.

[0039] Example 1

[0040] 5mmol Mn(CH3COO)2·4H2O and 5mmol Cd(CH3COO)2·2H2O were dissolved in distilled water and stirred for 30min to fully dissolve. Then, thioacetamide (TAA, 10mmol) was added and stirred to mix evenly. The mixture was transferred to a reactor lined with polytetrafluoroethylene. The reactor was placed in an oven at 160°C for 24h. After the reaction was completed, it was cooled to room temperature. The solid in the reactor was washed three times with deionized water and anhydrous ethanol and dried at 60°C to obtain orange Mn 0.5 Cd 0.5 S powder (MCS).

[0041] 1 mmol AgNO3 and 1 mmol TAA were dispersed in 40 mL H2O and stirred for 20 min to mix evenly. The mixture was then transferred to a reactor lined with polytetrafluoroethylene and placed in an oven at 150°C for 2 h. After the reaction was completed, it was cooled to room temperature, and the solid in the reactor was washed and dried to obtain Ag2S.

[0042] The above Mn 0.5 Cd 0.5 The S catalyst and Ag2S catalyst were dissolved in 10 mL of deionized water and subjected to 240 W ultrasonic treatment for 1 h and stirring at 400 r / min for 4 h. The mixture was filtered, washed and dried at room temperature to obtain an orange powder, which was Ag2S / Mn 0.5 Cd 0.5 S composite catalyst. The mass of Ag2S is Mn 0.5 Cd 0.5 3% of S mass.

[0043] 3%Ag2S / Mn 0.5 Cd 0.5 Application method of S composite catalyst:

[0044] (1) Weigh 2 mg of 3% Ag2S / Mn 0.5 Cd 0.5 S composite catalyst, add 18mL water, ultrasonic dispersion for half an hour, so that the catalyst is evenly dispersed in the water. Then add 2mL of 0.35M Na2S, 0.25MNa2SO3 mixed solution as sacrificial agent, then pass N2 for half an hour, and finally seal for 2h under ultrasound (240W) and light (55W xenon lamp simulated sunlight). After the experiment, extract 0.5mL of gas in the tube, detect the peak area with gas chromatograph, calculate the H2 production rate, and the H2 production rate is 26.25mmol / (g·h) after analysis and calculation.

[0045] Using the same method, the test results showed that the H2 production rate of MCS was 5.57 mmol / (gh) and the CO production rate was 3.21 μmol / (g·h).

[0046] (2) Weigh 2 mg of 3% Ag2S / Mn 0.5 Cd 0.5S composite catalyst, add 18mL of water, ultrasonically disperse for half an hour to make the catalyst evenly dispersed in the water. Then add 2mL of a mixed solution of 0.35M Na2S and 0.25MNa2SO3 as a sacrificial agent, then pass CO2 for half an hour, and finally seal for 2h under ultrasound (240W) and light (55W xenon lamp simulated sunlight). After the test, extract 0.5mL of gas in the tube, detect the peak area with a gas chromatograph, calculate the CO production rate, and the CO production rate is 14.49μmol / (g·h) after analysis and calculation.

[0047] Example 2

[0048] Compared with Example 1, the difference is that the mass of Ag2S added in the preparation process is Mn 0.5 Cd 0.5 The other preparation methods are the same as those in Example 1.

[0049] The application method is the same as that of Example 1. The 1% Ag2S / Mn prepared in Example 2 0.5 Cd 0.5 The S composite catalyst produced H2 at a rate of 18.76 mmol / (g·h); and produced CO at a rate of 8.12 μmol / (g·h).

[0050] Example 3

[0051] Compared with Example 1, the difference is that the mass of Ag2S added in the preparation process is Mn 0.5 Cd 0.5 The other preparation methods are the same as those in Example 1.

[0052] The application method is the same as that of Example 1. The 5% Ag2S / Mn prepared in Example 3 0.5 Cd 0.5 The H2 production rate of the S composite catalyst is 15.38 mmol / (g·h); the CO production rate is 7.08 μmol / (g·h).

[0053] Example 4

[0054] Compared with Example 1, the difference is that the mass of Ag2S added in the preparation process is Mn 0.5 Cd 0.5 The other preparation methods are the same as those in Example 1.

[0055] The application method is the same as that of Example 1. The 7% Ag2S / Mn prepared in Example 4 0.5 Cd 0.5 The H2 production rate of the S composite catalyst is 11.81 mmol / (g·h); the CO production rate is 5.17 μmol / (g·h).

[0056] Comparative Example 1

[0057] Compared with Example 1, the difference is that the application method is changed from ultrasound (240W) and light (55W xenon lamp simulated sunlight) to ultrasound (240W), and the rest is the same as Example 1. 3% Ag2S / Mn 0.5 Cd 0.5 The H2 production rate of S catalyst is 76.85 μmol / (g·h).

[0058] Comparative Example 2

[0059] Compared with Example 1, the difference is that the application method is changed from ultrasound (240W) and light (55W xenon lamp simulated sunlight) to light only (55W xenon lamp simulated sunlight), and the rest is the same as Example 1. 3% Ag2S / Mn 0.5 Cd 0.5 The H2 production rate of S catalyst is 16.61mmol / (g·h).

[0060] Comparative Example 3

[0061] Compared with Example 1, the difference is that the molar ratio of the added Mn(CH3COO)2·4H2O and Cd(CH3COO)2·2H2O is 0.2:0.8, and the prepared composite catalyst is recorded as 3% Ag2S / Mn 0.2 Cd 0.8 S.

[0062] The application method is the same as in Example 1. The prepared 3% Ag2S / Mn 0.2 Cd 0.8 The H2 production rate of the S composite catalyst is 0.43mmol / (g·h).

[0063] Comparative Example 4

[0064] Compared with Example 1, the difference is that the molar ratio of the added Mn(CH3COO)2·4H2O and Cd(CH3COO)2·2H2O is 0.3:0.7, and the prepared composite catalyst is recorded as 3% Ag2S / Mn 0.3 Cd 0.7 S.

[0065] The application method is the same as in Example 1. The prepared 3% Ag2S / Mn 0.3 Cd 0.7 The hydrogen production rate of the S composite catalyst is 0.5 mmol / (g·h).

[0066] Comparative Example 5

[0067] Compared with Example 1, the difference is that the molar ratio of the added Mn(CH3COO)2·4H2O and Cd(CH3COO)2·2H2O is 0.4:0.6, and the prepared composite catalyst is recorded as 3% Ag2S / Mn 0.4 Cd 0.6 S.

[0068] The application method is the same as in Example 1. The prepared 3% Ag2S / Mn 0.4 Cd 0.6 The hydrogen production rate of the S composite catalyst is 0.56 mmol / (g·h).

[0069] Comparative Example 6

[0070] Compared with Example 1, the difference is that the molar ratio of the added Mn(CH3COO)2·4H2O and Cd(CH3COO)2·2H2O is 0.6:0.4, and the prepared composite catalyst is recorded as 3% Ag2S / Mn 0.6 Cd 0.4 S.

[0071] The application method is the same as in Example 1. The prepared 3% Ag2S / Mn 0.6 Cd 0.4 The hydrogen production rate of the S composite catalyst is 19.47 mmol / (g·h).

[0072] Comparative Example 7

[0073] Compared with Example 1, the difference is that the molar ratio of the added Mn(CH3COO)2·4H2O and Cd(CH3COO)2·2H2O is 0.7:0.3, and the prepared composite catalyst is recorded as 3% Ag2S / Mn 0.7 Cd 0.3 S.

[0074] The application method is the same as in Example 1. The prepared 3% Ag2S / Mn 0.7 Cd 0.3 The hydrogen production rate of the S composite catalyst is 7.59 mmol / (g·h).

[0075] Although the present invention has been described in conjunction with the preferred embodiments, the present invention is not limited to the above embodiments, and it should be understood that the appended claims summarize the scope of the present invention. Under the guidance of the inventive concept, those skilled in the art should be aware that certain changes made to the various embodiments of the present invention will be covered by the spirit and scope of the claims of the present invention.

Claims

1. Ag2S / Mn 0.5 Cd 0.5 S composite catalyst, characterized in that The composite catalyst is composed of Mn 0.5 Cd 0.5 The heterojunction structure formed by the composite of S and Ag2S, Ag2S is Mn 0.5 Cd 0.5 S 1-7% by mass.

2. An Ag2S / Mn as claimed in claim 1 0.5 Cd 0.5 The method for preparing the S composite catalyst is characterized in that: Mn 0.5 Cd 0.5 S and Ag2S were dissolved in a solvent, and after ultrasonication and stirring, they were filtered, washed, and dried to obtain Ag2S / Mn 0.5 Cd 0.5 S composite catalyst; the solvent is deionized water, anhydrous ethanol, or a mixed solvent of deionized water and anhydrous ethanol; the ultrasonic power is 240W, and the ultrasonic time is 1h; the stirring speed is 400r / min, and the stirring time is 4h.

3. Ag2S / Mn as claimed in claim 2 0.5 Cd 0.5 The method for preparing the S composite catalyst is characterized in that: The Mn 0.5 Cd 0.5 The preparation method of S is as follows: Mn(CH3COO)2·4H2O and Cd(CH3COO)2·2H2O are dissolved in deionized water, stirred until completely dissolved, then C2H5NS is added and stirred to mix evenly, and then the mixed solution is transferred to a reactor with a polytetrafluoroethylene liner and placed in an oven at 160°C for 24 hours. After the reaction is completed, it is cooled to room temperature, and the solid in the reactor is washed and dried to obtain orange Mn 0.5 Cd 0.5 S powder.

4. Ag2S / Mn as claimed in claim 3 0.5 Cd 0.5 The method for preparing the S composite catalyst is characterized in that: The molar ratio of Mn(CH3COO)2·4H2O, Cd(CH3COO)2·2H2O and C2H5NS is 1:1:

2.

5. The Ag2S / Mn according to claim 2 0.5 Cd 0.5 The method for preparing the S composite catalyst is characterized in that: The Ag2S preparation method is as follows: AgNO3 and TAA are dispersed in H2O, stirred and mixed evenly, and then the mixed solution is transferred to a reactor with a polytetrafluoroethylene liner, and allowed to stand in an oven at 150°C for 2 hours. After the reaction is completed, it is cooled to room temperature, and the solid in the reactor is washed and dried to obtain Ag2S.

6. Ag2S / Mn as claimed in claim 5 0.5 Cd 0.5 The method for preparing the S composite catalyst is characterized in that: The mass ratio of AgNO3 and TAA is 1:1 by mole.

7. An Ag2S / Mn as claimed in claim 1 0.5 Cd 0.5 The application of S composite catalyst is characterized by: The catalyst is used for piezoelectric photocatalytic production of H2; or for piezoelectric photocatalytic CO2 reduction production of CO.

8. Ag2S / Mn as claimed in claim 7 0.5 Cd 0.5 The application of S composite catalyst is characterized by: Ag2S / Mn 0.5 Cd 0.5 The S composite catalyst is added to the solvent and dispersed evenly, and then a sacrificial agent is added, followed by N2 or CO2, and piezoelectric photocatalysis is carried out to produce H2 or CO2 reduction to produce CO under ultrasound and light conditions.

9. Ag2S / Mn as claimed in claim 8 0.5 Cd 0.5 The application of S composite catalyst is characterized by: The solvent is: deionized water, anhydrous ethanol, or a mixed solvent of anhydrous ethanol and water; The concentrations of Na2S and Na2SO3 in the sacrificial agent solution are 0.35M and 0.25M respectively. The ultrasonic power is 240W, and the illumination adopts sunlight simulated by a 55W xenon lamp.

Citation Information

Patent Citations

  • Titanate nanotube composite type photocatalyst as well as preparation method and application thereof

    CN103599772A

  • Photocatalyst, photocatalyst film and their preparation methods and application

    CN108786806A

  • Mn0.5Cd0.5S / Ag / Bi2WO6 compound type photocatalyst with Z-type structure and preparation method thereof

    CN108855138A

  • Mn0. 5Cd0. 5S / Cu7S4 composite catalyst and application thereof in producing H2 through piezoelectric electro-catalysis

    CN117548125A